How do forensic inpatients' interpersonal sensitivity to dominance and perceptions of staff coercion impact upon anger and rates of aggression?. Issue 2 (6th April 2021) - Holley, Jessica; Tapp, James; Draycott, Simon
Abstract : Purpose: Coercive practices – which are used as means to manage violent/aggressive behaviour in secure forensic settings – have come under scrutiny in recent years due to their paradoxical effects on provoking further service user aggression and violence. Previous research has found relationships between increased service user aggression with both service users' interpersonal styles and perceptions of staff coercion (i.e. staff limit setting). This paper aims to investigate whether forensic service users' levels of interpersonal sensitivity to dominance increase levels of self-reported anger and rates of aggression towards staff through perceptions of staff coercion. Design/methodology/approach: In a cross-sectional quantitative study design, 70 service users were recruited from one high and two medium secure forensic hospitals. Standardised measures were completed by service users and recorded incident data was collected within the past year. Correlation and mediation analyses were run to investigate the relationship between study variables. Findings: A significant relationship was found between service users' interpersonal sensitivity to dominance and self-reported rates of anger, where forensic service users' who had higher levels of interpersonal sensitivity to others' dominance were likely to report higher rates of anger. No significant relationships were found between all other study variables. Practical implications: The findings from this study contradict previous research where coercive practices may not necessarily increase rates of aggression towards staff but, in the context of service users' interpersonal sensitivities to dominance, it may be more useful to consider the way in which coercive practices are implemented. Originality/value: There is a gap in the literature, which looks at the way in which forensic service users perceive coercive practices in relation to their interpersonal sensitivities and whether this too has an impact upon service user aggression.